Evaluation of ground motions and seismic performance of RC buildings after 2023 Kahramanmaras earthquakes: design and construction deficiencies - Ince, Elif Gokce; Cakil, Burak; Simsek, Mutlu; Ince, Ozan (Springer, 2026)
Two major earthquakes occurred on the East Anatolian Fault Zone in T & uuml;rkiye on February 6, 2023. The epicenter of these earthquakes was Pazarc & imath;k and Elbistan, distinct from Kahramanmara & scedil; province. These earthquakes occurred on the same day, 9 hours apart, and effected a very large area. This study evaluates the damage in reinforced concrete buildings during the Kahramanmara & scedil; earthquakes. Firstly, this study examined T & uuml;rkiye's seismicity, fault lines, and recent earthquakes in T & uuml;rkiye. Then, the fault rupture of the Kahramanmara & scedil; earthquakes and the affected regions from these earthquakes were examined. Acceleration records of the Pazarc & imath;k and Elbistan earthquakes were evaluated by comparing them with the T & uuml;rkiye Building Earthquake Code-2018 (TBEC-2018). These acceleration records were compared with the largest earthquake (DD1) and design earthquake (DD2) defined in TBEC-2018. Requirements for earthquake-resistant building design and the deficiencies in the current T & uuml;rkiye building stock were discussed. Damages in RC buildings were evaluated in terms of design and construction perspectives. It has been observed that deficiencies are frequently made in the application of reinforcement details in RC buildings. Brittle shear damage has been commonly observed in reinforced concrete buildings, even though they are expected to behave ductile. Design and construction deficiencies have been observed to be widespread even in buildings still under construction.
Keywords: Kahramanmaras earthquakes; Earthquake damages; Reinforced concrete buildings; Structural failure; Seismic vulnerability